Arahan Spasial Pengembangan Kawasan Agropolitan di Kecamatan Belitang Kabupaten Ogan Komering Ulu Timur - Tama Hariansyah Putra; Annisa Mu'awanah Sukmawati (Universitas Pakuan, 2025)
Belitang Sub-district is one of the sub-districts in Ogan Komering Ulu (OKU) Timur Regency which has competitive agricultural potential and potential to develop as an agropolitan area. However, Belitang Sub-district has problems in infrastructure and distribution facilities between sub-districts. This research aims to formulate the spatial directions for developing an agropolitan area in Belitang District. Data was collected through agency surveys, observations, interviews, and literature reviews. Data analysis techniques used in this study are land suitability scoring analysis, Location Quotient (LQ) analysis, and Scalogram analysis. The study revealed that Belitang Sub-district was included as one of the highest economic value areas in OKU Timur Regency and positioned as the center of the Independent Integrated City strategy area. This condition could support the development of an agropolitan area in Belitang Sub-district. The development of agropolitan areas should be directed at improving the condition of facilities and infrastructure, such as road networks and economic facilities to support the integration of upstream and downstream agropolitan activities.